[Pt(bipy)(ONO2)2] and [{(bipy)Pt(μ-O2NO)2Pt(bipy)}2](NO3)4: Empirically identical but structurally distinct complexes obtained from a basic aqueous solution of [Pt(bipy)2](NO3)2. (7th July 2017) - Lo, Warrick K.C.; Shepherd, Rebecca J.; Stranger, Robert; Blackman, Allan G.; Cavigliasso, Germán
Graphical abstract: After over 40 years of trying, X-ray quality crystals have finally been isolated from a basic aqueous solution containing the [Pt(bipy)2 ](NO3 )2 ·H2 O complex. The crystal structures of hydrated [Pt(bipy)(ONO2 )2 ] and [{(bipy)Pt(μ-O2 NO)2 Pt(bipy)}2 ](NO3 )4 show that deligation of one of the bipy ligands in the [Pt(bipy)2 ] 2+ cation can occur relatively easily. Abstract: Vapour diffusion of acetonitrile into a basic aqueous solution of [Pt(bipy)2 ](NO3 )2 ·H2 O results in slow crystallisation of a mixture of the monomeric complex [Pt(bipy)(ONO2 )2 ]·5.25H2 O and the tetrameric complex [{(bipy)Pt(μ-O2 NO)2 Pt(bipy)}2 ](NO3 )4 ·8.5H2 O, the structures of which were confirmed by X-ray crystallography. Calculations on the tetrameric complex show that the central Pt–Pt bond is weak, as evidenced by the fact that inclusion of dispersion forces is required to prevent the cation from dissociating into two [(bipy)Pt(μ-O2 NO)2 Pt(bipy)] 2+ dimers. Isolation of the monomeric and tetrameric complexes shows that one of the bipy ligands in the [Pt(bipy)2 ] 2+ cation is easily displaced in basic aqueous solution. This displacement may be a consequence of OH − attack at the Pt ion.